2015
DOI: 10.1080/03601234.2015.1011971
|View full text |Cite
|
Sign up to set email alerts
|

Elemental distribution and uptake by watercress (Nasturtium aquaticum)as a function of water quality

Abstract: Watercress (Nasturtium aquaticum), is an edible plant commonly found in Southern Africa, which grows both in terrestrial and aquatic environments. The elemental concentrations in the plant and surrounding water (growth solution) were investigated to determine the plants nutritional value and to establish impact of water quality on elemental uptake by the plant. The concentrations in the leaves, roots and water were analyzed at eight different sites along the east coast of KwaZulu-Natal, South Africa (30.0000° … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Watercress ( Nasturtium officinale , WC) is a plant that grows in arid and aquatic situations and is rich in vitamins (such as A, B, C, K, E, and folic acid), ions/elements (such as iron, chromium, calcium, magnesium, phosphorus, iron, potassium, zinc, and sodium), and bioactive substances (for instance, β -carotene, lutein, and quercetin). It is used to treat diabetes, anemia, and eczema, as well as renal and hepatic disorders [ 18 – 20 ]. Previous studies showed that WC reduces the risk of colon, lung, lymphatic, and prostate cancers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Watercress ( Nasturtium officinale , WC) is a plant that grows in arid and aquatic situations and is rich in vitamins (such as A, B, C, K, E, and folic acid), ions/elements (such as iron, chromium, calcium, magnesium, phosphorus, iron, potassium, zinc, and sodium), and bioactive substances (for instance, β -carotene, lutein, and quercetin). It is used to treat diabetes, anemia, and eczema, as well as renal and hepatic disorders [ 18 – 20 ]. Previous studies showed that WC reduces the risk of colon, lung, lymphatic, and prostate cancers [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 12 PTEs were measured using inductively coupled plasma optical emission spectroscopy (ICP-OES). The water samples were digested with 70% nitric acid using open vessel digestion, following a modified method from Kisten et al [51]. The digested samples were filtered and diluted to 25 mL with double-distilled water and then stored in the refrigerator for the PTE analysis.…”
Section: Applying the Spr Model To The Sampling Sites In The Mlm Area...mentioning
confidence: 99%